The remaking of the British working class, 1840-1940 - Savage, Michael, 1959- (Historical connections., 1994)
This textbook provides a comprehensive introduction to the working class in Britain in the years after 1850, and breaks new ground in showing how social mobility and urban change affected working class formation.